(untitled) (International journal of artificial intelligence, 2025)
This article explores the challenges of visualizing ideas and impressions in fine arts. It examines the role of visual thinking in artistic creativity, analyzes visualization methods in contemporary art, and assesses their effectiveness. The discussion highlights the integration of traditional and digital technologies, compositional solutions, and artistic-aesthetic requirements. The study concludes with recommendations for effective methods of visualizing ideas and information in fine arts.